Thioarsenate Formation Coupled with Anaerobic Arsenite Oxidation by a Sulfate-Reducing Bacterium Isolated from a Hot Spring - Wu, Geng; Huang, Liuqin; Jiang, Hongchen; Peng, Yue’e; Guo, Wei; Chen, Ziyu; She, Weiyu; Guo, Qinghai; Dong, Hailiang (Frontiers in Microbiology, 2017)
Thioarsenates are common arsenic species in sulfidic geothermal waters, yet little is known about their biogeochemical traits. In the present study, a novel sulfate-reducing bacterial strain Desulfotomaculum TC-1 was isolated from a sulfidic hot spring in Tengchong geothermal area, Yunnan Province, China. The arxA gene, encoding anaerobic arsenite oxidase, was successfully amplified from the genome of strain TC-1, indicating it has a potential ability to oxidize arsenite under anaerobic condition. In anaerobic arsenite oxidation experiments inoculated with strain TC-1, a small amount of arsenate was detected in the beginning but became undetectable over longer time. Thioarsenates (AsO4-xSx2- with x = 1-4) formed with mono-, di- and tri-thioarsenates being dominant forms. Tetrathioarsenate was only detectable at the end of the experiment. These results suggest that thermophilic microbes might be involved in the formation of thioarsenates and provide a possible explanation for the widespread distribution of thioarsenates in terrestrial geothermal environments.